(untitled) (Journal of Contemporary Philology, 2019)
The paper examines newspaper headlines written in Macedonian with the aim to determine their syntactic characteristics. The analysis of the collected examples shows thatthe headlines written in standard Macedonian have identical syntactic features with those in other languages already identified in previous research. However, the headlines analyzed in this paper also display certain specific features attributable to the syntactic constructions characteristic of Macedonian.The findings identified several features, such as: maximum condensed information leading to syntactic ambiguity of the headlines, depending on whether the headlines are treated as a simple or compound sentence; reduction of the information into a single,complexsyntagma, which poses the dilemma of whether the activity coded by the predicate is completed or not; the dual interpretation of the participial adjective, which determines the sentence as active or passive; the use of asyndetic structures and other types of subordination strategies in complex sentences, which strengthens their syntactic ambiguity and contributes to their over-informativeness.